PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL DAN DANA ALOKASI UMUM TERHADAP PERTUBUHAN EKONOMI DI PROVINSI ACEH - Muhammad Havis; Rizki Imam Maulana; Wahyuni Siregar; Puti Andiny; Safuridar Safuridar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Economic growth is an important indicator that reflects the success of regional development. This study aims to analyze the effect of Regional Own-Source Revenue (PAD), Capital Expenditure, and General Allocation Fund (DAU) on economic growth in Aceh Province. The research employs a quantitative approach using time series data from 2009 to 2023, obtained from the Central Bureau of Statistics (BPS). Data were analyzed using multiple linear regression with the Eviews 9 software. The results show that PAD and DAU have a positive and significant effect on economic growth, while Capital Expenditure has a negative and insignificant effect. Simultaneously, the three variables have a significant impact on economic growth with a coefficient of determination (R²) of 78.44%. These findings suggest that local governments need to optimize PAD and manage transfer funds more productively to accelerate sustainable economic growth in Aceh Province